A BRIEF SURVEY ON SYMBOLIC EXECUTION TEST-SELECTION TECHNIQUES - Nivethithaa, K.K; Krishnapriya, V (International Journal of Computer Sciences and Engineering, 2025)
Symbolic execution techniques decrease the cost of path redundancy by choosing a separation of an existing test suite to use in retesting a customized program. Over the history, Eliminating Path Redundancy via Postconditioned Symbolic Execution techniques has been described in the literature. This paper aims to present a brief survey on symbolic executions in black-box and white-box regression testing under the Software testing and learning techniques that are in use in today's software engineering of verification and validation tasks. Number of comparative study has been performed to evaluate the performance of predictive accuracy on the test cases and the outcome discloses that Bidirectional Symbolic Analysis for Effective Branch Testing method outperforms having better performance other predictive methods are not performing well